Cognitive rehabilitation for memory deficits after stroke (review) - das Nair, Roshan; Cogger, Heather; Worthington, Esme; Lincoln, Nadina (Cochrane Collaboration, 2016)
Background Memory problems are a common cognitive complaint following stroke and can potentially affect ability to complete functional activities. Cognitive rehabilitation programmes either attempt to retrain lost or poor memory functions, or teach patients strategies to cope with them. Some studies have reported positive results of cognitive rehabilitation for memory problems, but the results obtained from previous systematic reviews have been less positive and they have reported inconclusive evidence. This is an update of a Cochrane review first published in 2000 and most recently updated in 2007.